The Relationship Between Mesenchymal Stem Cells and Tumor Dormancy - Zhao, Linxian; Zhang, Kai; He, Hongyu; Yang, Yongping; Li, Wei; Liu, Tongjun; Li, Jiannan (Frontiers in Cell and Developmental Biology, 2021)
Tumor dormancy, a state of tumor, is clinically undetectable and the outgrowth of dormant tumor cells into overt metastases is responsible for cancer-associated deaths. However, the dormancy-related molecular mechanism has not been clearly described. Some researchers have proposed that cancer stem cells (CSCs) and disseminated tumor cells (DTCs) can be seen as progenitor cells of tumor dormancy, both of which can remain dormant in a non-permissive soil/niche. Nowadays, research interest in the cancer biology field is skyrocketing as mesenchymal stem cells (MSCs) are capable of regulating tumor dormancy, which will provide a unique therapeutic window to cure cancer. Although the influence of MSCs on tumor dormancy has been investigated in previous studies, there is no thorough review on the relationship between MSCs and tumor dormancy. In this paper, the root of tumor dormancy is analyzed and dormancy-related molecular mechanisms are summarized. With an emphasis on the role of the MSCs during tumor dormancy, new therapeutic strategies to prevent metastatic disease are proposed, whose clinical application potentials are discussed, and some challenges and prospects of the studies of tumor dormancy are also described.